Digital Transformation in Islamic Banking: A Literature Study on Fintech Innovation, Open Banking, and Sharia Compliance in the Industrial Era 5.0 - Irfan Saefuloh Saefuloh; Nina Ismiyanti Ismiyanti; Meri Rusdiani Rusdiani; Aep Saefuddin Saefuddin (Masoem University, 2026)
Digital transformation in banking sharia is inevitability in the Industry 5.0 era, when collaboration humans and technology must still in harmony with efficiency operational, innovation, and compliance to principle Sharia. Research This aim examine literature scientific related integration digitalization in banking sharia, with focus on fintech innovation, open banking implementation, and compliance regulations sharia in Indonesia. The method used is studies literature qualitative with analysis content to publication national and international 2018–2025 period. Study results show that digital innovations such as sharia mobile banking application, halal digital wallet, and integration fintech solutions are capable increase efficiency, expanding inclusion finance, as well as strengthen Power competition banking sharia at the global level. However, a number of challenge Still appear, especially related human resource readiness, regulations digital contract based sharia, and the need for sharia audits that are supported technology. The implementation of open banking requires collaboration strong between regulators, institutions finance, and fintech players to ensure equality, transparency, and protection aligned consumers with principle maq??id al- shar?'ah. Study This conclude that success digital transformation of banking sharia depends on integration harmonious between innovation technology, spiritual values, and governance adaptive sharia. This study also provides contribution theoretical about the concept of sharia digital governance as well as recommendation practical for regulators and industry banking use build ecosystem finance inclusive, ethical, and sustainable sharia in the digital era.